Dinâmica populacional de Triozoida limbata, Costalimaita ferruginea e inimigos naturais em pomar orgânico e convencional de goiaba - Duarte, Rogerio Teixeira [UNESP]; Galli, Julio Cesar [UNESP]; Pazini, Wilson Carlos [UNESP]; Calore, Ricardo Aparecido [UNESP] (Soc Brasileira Fruticultura, 2012)
We investigated the population dynamics of Triozoida limbata (Hemiptera: Triozidae) and Costalimaita ferruginea (Coleoptera: Chrysomelidae) and its correlation with the population of natural enemies in organic and conventional orchard of guava. The experiments were performed in two distinct orchards of guava in the 2010/2011 harvest. For monitoring pests and natural enemies, we installed five yellow sticky traps in each orchard. To obtain the correlation between population densities of pests with natural enemies, we used Pearson linear correlation analysis (SAS). The population density of T. limbata remained low, and reaches the top in October in organic orchard of guava. The main pest in conventional orchard of guava was T. limbata and population reaches the top several times. The damage caused by T. limbata in new leaves of guava was more pronounced in conventional orchard. There was a low population density of C. ferruginea in both orchards; however we observed that the population reaches the top in November in organic orchard. The species C. ferruginea caused higher damage in young leaves of guava tree in organic orchard. The highest population density of natural enemies was observed in organic orchard, which presented positive correlation between T. limbata and the coccinellid predator Scymnus spp.
Population dynamics of Triozoida limbata, Costalimaita ferruginea and natural enemies in organic and conventional orchard of guava
Keywords: Integrated pest management; monitoring; Conduction of the culture; Psidium guajava L.